2010
DOI: 10.1161/circulationaha.109.923383
|View full text |Cite|
|
Sign up to set email alerts
|

PLA2G7 Genotype, Lipoprotein-Associated Phospholipase A 2 Activity, and Coronary Heart Disease Risk in 10 494 Cases and 15 624 Controls of European Ancestry

Abstract: Background Higher Lp-PLA2 activity is associated with increased risk of coronary heart disease (CHD), making Lp-PLA2 a potential therapeutic target. PLA2G7 variants associated with Lp-PLA2 activity could evaluate whether this relationship is causal. Methods and Results A meta-analysis including a total of 12 studies (5 prospective, 4 case-control, 1 case-only and 2 cross-sectional, n=26,118) was undertaken to examine the association of: (i) LpPLA2 activity vs. cardiovascular biomarkers and risk factors and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 36 publications
4
90
0
Order By: Relevance
“…In a Taiwanese cohort, A379V was associated with increased risk of MI and increased severity of CAD ( 138 ). In contrast, a study of European Caucasians revealed reduced risk of MI in homozygotes for A379V ( 158 ), but metaanalyses of European Caucasian populations reported no association with CHD risk ( 56,156 ). In South Koreans, a similar lack of association between A379V and CVD disease was reported ( 137 ).…”
Section: Lp-pla 2 Polymorphisms and Cadmentioning
confidence: 87%
See 1 more Smart Citation
“…In a Taiwanese cohort, A379V was associated with increased risk of MI and increased severity of CAD ( 138 ). In contrast, a study of European Caucasians revealed reduced risk of MI in homozygotes for A379V ( 158 ), but metaanalyses of European Caucasian populations reported no association with CHD risk ( 56,156 ). In South Koreans, a similar lack of association between A379V and CVD disease was reported ( 137 ).…”
Section: Lp-pla 2 Polymorphisms and Cadmentioning
confidence: 87%
“…In contrast to the V279F allele associated primarily with Asian populations, three relatively well-studied nonsynonymous Lp-PLA 2 polymorphisms (R92H, I198T, and A379V) have been observed in all populations studied so far ( 142,156 ). The variants have been functionally characterized using molecular approaches ( 157 ).…”
Section: Lp-pla 2 Polymorphisms and Cadmentioning
confidence: 99%
“…Similarly, although data from epidemiological and clinical studies supported a potentially important role of lipoprotein-associated phospholipase A2 in atherosclerosis and its sequelae, 74,75 the genetic variants near PLA2G7 and CETP associated with LP-PLA2 levels and activity did not confer CAD risk. 76,77 In accord with these findings, the results of phase III randomized controlled trials of inhibitors of these enzymes (varespladib 78 and darapladib 79 ) were also negative. A closer inspection of MR data before drug design and initiation of clinical trials could, thus, help to mitigate the high costs of drug development.…”
Section: Mendelian Randomizationmentioning
confidence: 89%
“…[9][10][11] Previous investigations of genetic determinants of plasma Lp-PLA 2 focused on the gene that encodes Lp-PLA 2 (PLA2G7) and genes encoding other inflammatory molecules. 8,12,13 A genome-wide association study (GWAS) of circulating Lp-PLA 2 was performed among 6688 participants of the Framingham Heart Study (FHS).…”
Section: Clinical Perspective On P 685mentioning
confidence: 99%